Transformation in Indian Engineering Education through Academic Autonomy to High Performing Faculty Teams - Thanikachalam, Vedhathiri (Journal of Engineering Education Transformations, 2016)
In the twenty first century, engineering education in India has to contribute to the fast developing economy through high end knowledge and human capital. The leaders need high performing faculty and staff teams for sustenance of excellence. The Board of Governors, CEO, administrators and the faculty association have to support the high performers.Through research studies, it is found that the transformation in engineering education is desirable only through cultural change and decentralization of administration. The sustenance of excellence is possible through delegation and empowerment with adequate accountability. The traditional water tight compartments and bureaucratic approaches would not support excellence. There is a need for multidisciplinary approach for solving many field problems, and the faculty needs of appropriate interdisciplinary teams. To develop industry relevant programs in engineering and technology, institute's vision and mission not only relevant but also essential for sustaining the initial efforts. Besides resources, faculty members need supportive leadership and linkages with the governments, industry and national laboratories. The institutes have to redefine the doctrines which would accelerate the growth. Excellence has to be recognized and supported. There is a need for periodical assessment of institute's culture and views of the faculty. Transformation and reengineering of the departments have to be undertaken periodically so that the faculty may be facilitated for growth.